1964
DOI: 10.1139/o64-059
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Chromium-51 as a Sensitive Quantitative Criterion of Early Radiation Damage to Rat Thymocytes

Abstract: The uptake of Crsl-chromate by thymocytes in suspension can be used as a sensitive quantitative criterion for the evaluation of early radiation damage to these cells, often under situations where other methods of assessing cell death such as morphological changes do not yield valid results. 'I'he development of a radiation lesion is characterized by a reduction in the uptake of Cr5l, which in vitro can be detected 1 hour following irradiation and with doses as low as 25 rads. By means of this technique thymocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1964
1964
1991
1991

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…During the course of this work it was observed that certain compounds in concentrations of 10-20 m M were highly toxic to Ehrlich ascites cells as measured by their subsequent growth, if left in coiltact with them for periods of time as short as 30 minutes. Similar findings have been reported for thymocytes in earlier work (20) and for embryonic heart cells (21) and strain-L mouse fibroblasts (22). Consequently all cell Can.…”
Section: Resultssupporting
confidence: 90%
“…During the course of this work it was observed that certain compounds in concentrations of 10-20 m M were highly toxic to Ehrlich ascites cells as measured by their subsequent growth, if left in coiltact with them for periods of time as short as 30 minutes. Similar findings have been reported for thymocytes in earlier work (20) and for embryonic heart cells (21) and strain-L mouse fibroblasts (22). Consequently all cell Can.…”
Section: Resultssupporting
confidence: 90%
“…cells is thus markedly enhanced by raising the oxygen tension over a range where no further effect on nuclear damage is observed . Oxygen enhancement ratios higher than those observed in cell survival and nuclear damage studies have been reported for radiation-induced changes in other membrane parameters (Scaife and Vittorio 1964, Watkins 1970, Cramp, Watkins and Collins 1972 . The evidence to date supports Alper's theory that biological membranes are major sites for the oxygen effect.…”
Section: Discussionmentioning
confidence: 76%
“…Cra studies on a cellular basis have already been carried out. I t was found that Cr51 uptalte by thymocytes is an active cellular uptake depending upon the integrity of the cell and that the uptake of Cr51 chromate by thymocytes in suspension can be used as a sensitive quantitative criterioil for the evaluation of early radiation damage to these cells (13). Other studies are in progress in an attempt to determine the early and late effects of Xirradiation and protective compounds on cell suspensions (i.e.…”
Section: Heartmentioning
confidence: 99%